Colostomy and ileostomy care in nursing education: Which is more effective: Synchronous or asynchronous? - Yildiz, Tulin; Erden, Dilek; Sabirli, Cagla; Malak, Arzu (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the effects of synchronous and asynchronous training on the academic achievements and e-learning attitudes of nursing student trained in colostomy and ileostomy care. Method: The quasi-experimental, descriptive study was conducted at the Nursing Department of a health facility after approval from the Tekirdag Namik Kemal University, Tekirdag, Turkey, from May to June 2020, and comprised nursing students who were divided in intervention group A and control group B. Those in group A were given synchronous training on colostomy and ileostomy care using active learning techniques on an online platform, while those group B received their training only asynchronously. Data was collected using Colostomy and Ileostomy Knowledge Test, and the e-Learning Attitude Scale at baseline and post-intervention. Data was analysed using SPSS 17. Results: Of the 154 students, there were 77(50%) in each of the two groups. Overall, 53(34.4%) students were in 2nd grade, 60(39%) in 3rd, and 41(26.6%) in 4th grade of their training. The mean age of the sample was 21.50±1.10 years. Post-intervention mean scores for knowledge and e-learning tendency were significantly higher in both the groups compared to the baseline (p<0.01). Mean score for e-learning avoidance was significantly lower and mean knowledge score was significantly higher in group A than group B (p<0.05). Conclusion: The application of active learning activities among students was found to have a positive effect on nursing education compared to asynchronous teaching. Key Words: Nursing student, Distance learning, Academic success, E-learning.